Prosecutorial Use of Expert Testimony in Domestic Violence Cases: From Recantation to Refusal to Testify - Rogers, Audrey (Columbia Journal of Gender and Law, 1998)
Mandatory arrest laws and no-drop policies have greatly increased the number of batterers being prosecuted. Unlike conventional cases, however, where prosecutors rely on the cooperation and participation of complaining witnesses to obtain convictions, in domestic violence cases prosecutors are often faced with exceptional challenges. Such challenges include victims who refuse to testify, who recant previous statements, or whose credibility is attacked by defense questions on why they remained in a battering relationship. To explain the behavior of such victims, prosecutors rely increasingly on expert testimony on battering and its effects. While the use of expert testimony on battering and its effects has been widely used by women claiming that they have killed their abusers in self-defense, it is only in the last few years that prosecutors have made significant efforts to use experts when prosecuting batterers. Until 1990, appellate courts in only a handful of jurisdictions had considered whether prosecutors may use expert testimony on battering and its effects in a domestic violence prosecution. Between 1991 and 1997, however, appellate courts in at least thirteen more jurisdictions ruled on the admissibility of expert testimony to explain a battering victim’s puzzling behavior at or before trial. All of those jurisdictions, except Ohio, approved of prosecutorial use of expert testimony.